1998
DOI: 10.1053/euhj.1998.1090
|View full text |Cite
|
Sign up to set email alerts
|

Increased left ventricular systolic function in insulin dependent diabetic patients with normal albumin excretion

Abstract: Alterations in cardiovascular function may be an aetiological factor for the development of microalbuminuria in patients with insulin-dependent diabetes mellitus. We studied cardiac function with echocardiography in relation to the degree of albuminuria in 27 insulin-dependent diabetes mellitus patients and 13 healthy subjects. Patients were grouped according to urinary albumin excretion: <20 g . min 1 (normoalbuminuric), and 20 to 200 g . min 1 (microalbuminuric). None were or had been treated with cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…in pharmacological RAAS inhibition (40,41). Importantly, and consistent with previous work in this area, blood pressure was higher in T1D-H (4,42,43). Although this blood pressure elevation within the normal range in T1D-H could be attributed to an elevated systemic sympathetic tone (43), our results suggest that decreased FE Na in euglycemic states may also contribute through increases in total body sodium (44).…”
Section: Discussionsupporting
confidence: 89%
“…in pharmacological RAAS inhibition (40,41). Importantly, and consistent with previous work in this area, blood pressure was higher in T1D-H (4,42,43). Although this blood pressure elevation within the normal range in T1D-H could be attributed to an elevated systemic sympathetic tone (43), our results suggest that decreased FE Na in euglycemic states may also contribute through increases in total body sodium (44).…”
Section: Discussionsupporting
confidence: 89%
“…Guglielmi et al reported significant changes in left ventricular morphology, impairment of cardiac diastolic function, altered vascular dilatory capacity, and higher daytime BP in patients with T1DM and microalbuminuria, on the absence of autonomic dysfunction [48]. Conversely, Christiansen et al showed that increased heart rate and cardiac contractility preexisted microalbuminuria, suggesting that the above factors may contribute to renal hyperperfusion and glomerular hyperfiltration, findings which are observed in T1DM patients, before the development of microalbuminuria [49]. Recently, it was suggested that the renin-angiotensin-aldosterone system might play a central role in the development and the progression of renal as well as cardiovascular impairment in patients with T1DM, while randomized, controlled trials demonstrated beneficial effects on renal and cardiovascular function of the use of angiotensin-converting enzyme inhibitors [50].…”
Section: Discussionmentioning
confidence: 99%
“…After exclusion of patients with coronary artery disease, systolic dysfunction is detected in 24% of T2D patients, as determined by strain analyses and peak systolic velocity measurements [69]. While studies have reported diastolic dysfunction in T1D patients [31, 174, 229], reports on systolic function in T1D are inconsistent, with some studies indicating preserved [168, 174] or increased systolic function [47]. The different results for studies with T1D and T2D patients may be a consequence of the selection of patients and the causative treatment of T1D patients with exogenous insulin, which may normalize the systemic milieu.
Fig.
…”
Section: Structural and Functional Consequencesmentioning
confidence: 99%